ANALISIS DAMPAK BAURAN KEBIJAKAN MONETER DAN MAKROPRUDENSIAL TERHADAP STABILITAS HARGA DAN STABILITAS SISTEM KEUANGAN DI INDONESIA - Hidayati, Nisaulfathona; Sugiyanto, FX (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2019)
The financial crisis that has happened has changed the perspective of the central banks in the world, including Indonesia in viewing that financial system stability is also important in addition to price stability. In achieving this goal, Bank Indonesia formulated a policy namely the Bank Indonesia Policy Mix which is the integration of monetary and macroprudential policies.This research aims to analyze the impact of the monetary and macroprudential policy mix on price stability and financial system stability in Indonesia. The analysis method applied in this study is Vector Error Correction Model (VECM) and Granger Causality. The results of the study show that both monetary and macroprudential policies can achieve price stability. In achieving financial system stability, monetary policy instruments take longer than macroprudential policies. The monetary and macroprudential policy mix instruments can reduce inflation volatility and exchange rate volatility so as to encourage price stability and financial system stability.